click below

click below

Normal Size Small Size show me how

# Distributive Prop

### Simplifying Expressions Using Distributive Property

Question | Answer |
---|---|

Simplify: 5(x + 8) | 5(x) + 5(8) = 5x + 40 |

Simplify: 11(3x + 5) | 11(3x) + 11(5) = 33x + 55 |

Simplify: (2x + 3)*9 | 2x(9) + 3(9) = 18x + 27 |

Simplify: -5(x + 10) | -5(x) + -5(10) = -5x - 50 |

Simplify: 7(4x - 8) | 7(4x) - 7(8) = 28x - 56 |

Simplify: -(7x + 11) | -1(7x) + -1(11) = -7x - 11 |

Simplify: -12(4 + 5x) | -12(4) + -12(5x) = -48 - 60x |

Simplify: -7(-5x - 4) | -7(-5x) - -7(4) = 35x + 28 |

Simplify: (4 - x)*-2 | -2(4) - -2(x) = -8 + 2x |

Simplify: 15(2x - 4) | 15(2x) - 15(4) = 30x - 60 |

Simplify: 10(-4x + 5) | 10(-4x) + 10(5) = -40x + 50 |

Simplify: -8(9 - 4x) | -8(9) - -8(4x) = -72 + 32x |

Simplify: 9(-12x - 2) | 9(-12x) - 9(2) = -108x - 18 |

Simplify: 9(-x + 7) | 9(-x) + 9(7) = -9x + 63 |

Simplify: -(-2x - 5) | -1(-2x) - -1(5) = 2x + 5 |